Speech disorders in primary progressive aphasia (PPA) - Katarzyna Mielniczek; Marta Lipiec; Diana Dołomisiewicz; Katarzyna Jóźwik; Aleksandra Kowalska (Kazimierz Wielki University, 2022)
Introduction : Primary progressive aphasia (PPA) is a group of neurodegenerative disorders whose main feature is speech and language dysfunction. There are three main forms of PPA - non-fluent variant - agrammatic (nfvPPA), semantic variant (svPPA) and logopenic variant (lvPPA). These include the canonical syndromes currently recognized by consensus diagnostic criteria. . Material and method : An overview of language disorders in primary progressive aphasia is presented. The impact on the conversation process and the patient's quality of life assessment was evaluated. The work was based on scientific publications posted on the scientific platform PubMed. Results : In order to diagnose PPA, criteria must be met, i.e., language difficulties are the main feature of the clinical picture, language difficulties are the main cause of disability in daily life, and that aphasia is the most significant disorder in the initial period of the disease. Conclusions : PPA significantly affects both the production and comprehension of speech. It affects the idea, content, construction and delivery of the patient's speech. In addition, it causes significant difficulties in the repetition of speech, both full sentences and words alone. Keywords : "speech disorders", "aphasia", "dysarthria", "primary progressive aphasia".